Spirit of the Renaissance [videorecording] - Barnes, John.; Gottlieb, Linda (Chicago Encyclopedia Britannica Educational Corp., 1979)
Explores the intellectual and artistic climate of Italy during the fourteenth and fifteenth centuries.
VHS.
Keywords: Renaissance -- Italy; Art, Renaissance